Pathophysiological Basis for the Formation of the Tumor Microenvironment - Horsman, Michael R.; Vaupel, Peter (Frontiers in Oncology, 2016)
Poor microenvironmental conditions are a characteristic feature of solid tumours. Such conditions occur because the tumor vascular supply, which develops from the normal host vasculature by the process of angiogenesis, is generally inadequate in meeting the oxygen and nutrient demands of the growing tumour mass. Regions of low oxygenation (hypoxia) is believed to be the most critical deficiency, since it has been well documented to play a significant role in influencing the response to conventional radiation and chemotherapy treatments, as well as influencing malignant progression in terms of aggressive growth and recurrence of the primary tumour and its metastatic spread. As a result, significant emphasis has been placed on finding clinically applicable approaches to identify those tumours that contain hypoxia and realistic methods to target this hypoxia. However, most studies consider hypoxia as a single entity, yet we now know that it is multifactorial. Furthermore, hypoxia is often associated with other microenvironmental parameters, such as elevated interstitial fluid pressure, glycolysis, pH, and reduced bioenergetic status, and these can also influence the effects of hypoxia. Here we review the various aspects of hypoxia, but also discuss the role of the other microenvironmental parameters associated with hypoxia.